Utilization of Parenteral Morphine by Application of ATC/DDD Methodology: Retrospective Study in the Referral Teaching Hospital - Dragojevic-Simic, Viktorija; Rancic, Nemanja; Stamenkovic, Dusica; Simic, Radoje (Frontiers in Public Health, 2017)
Background: Few studies analyzed the pattern of opioid analgesic utilization in hospital settings. The aim of this study was to determine the consumption pattern of parenteral morphine in patients hospitalized in the Serbian referral teaching hospital and to correlate it with utilization at the national and international level. Methods: In retrospective study, the required data were extracted from medical records of surgical patients who received parenteral morphine in the five-year period, from 2011 to 2015. We used the Anatomical Therapeutic Chemical Classification/Defined Daily Doses (ATC/DDD) international system for consumption evaluation. Results: While the number of performed surgical procedures in our hospital steadily increased from 2011 to 2015, the number of inpatient bed-days decreased from 2012. However, the consumption of parenteral morphine varied, and was not more than 0.867 DDD/100 bed-days in the observed period. Conclusion: Based on the available data, parenteral morphine consumption in our hospital was lower compared with international data. The low level of morphine use in the hospital was in accordance with national data. And compared with other countries, morphine consumption applied for medical indications in Serbia was low. Adequate legal provision in order to ensure the availability of opioids, better education and training of medical personnel, as well as multidisciplinary approach should enable more rational and individual pain management in the future, not only within the hospitals.